INOVASI PENGELOLAAN BANTUAN KEUANGAN : REFORMASI DAN REFORMULASI PENGALOKASIAN BANTUAN KEUANGAN BERSIFAT KHUSUS DARI PEMERINTAH KABUPATEN KEPADA PEMERINTAH DESA (STUDI KASUS PADA PEMERINTAH KABUPATEN PATI) - Fardani, Rizal; Kartiko, Sigit Wahyu; Heny, Wijayanti (Jurnal Akuntansi dan Bisnis, 2023)
The allocation of special financial assistance from the Pati Regency Government to the Village Government from 2017 to 2019 has always increased, in 2020 it has decreased due to refocusing related to handling the Covid-19 pandemic, in 2021 and 2022 it has increased again. The policy of allocating the financial aid budget is specific in nature to facilitate the aspirations of the main ideas of council members and regional heads for promises to their constituents. The purpose of this study is to analyze the policy on allocating special financial assistance from the Pati District Government to the Village Government. The design of this study is a qualitative research to gain insight into what is known and to obtain more complex details regarding phenomena in the management of financial aid. The results of the study concluded that this financial assistance should be used to stimulate funding for affairs in the Village which are a priority for the Regional Government in order to encourage the achievement of minimum service standards (SPM), and it is necessary to optimize the use of information technology in (1) formulating the allocation of special financial assistance, (2) determining the location of activities, in particular determining the variable recipients of financial assistance by (a) improving the SPM Indicators and improving the SPM data, (b) determining activities in the Village that will be funded by special financial assistance (c) determining the unit cost of activities in the Village that will be funded by special financial assistance, (d) determination of regions that have not yet achieved SPM, (d) determination of priority locations and (e) determination of output targets from proposed activities for next year and forward estimates for the next three years. Keywords: Innovation, Budget Constraints, Performance based budgeting